2001
DOI: 10.1182/blood.v98.6.1739
|View full text |Cite
|
Sign up to set email alerts
|

No difference in graft-versus-host disease, relapse, and survival comparing peripheral stem cells to bone marrow using unrelated donors

Abstract: The clinical results in 107 patients receiving a peripheral blood stem cell (PBSC) graft mobilized by granulocyte colonystimulating factor (G-CSF) from HLA-A, -B, and -DR-compatible unrelated donors were compared to 107 matched controls receiving unrelated bone marrow (BM) transplants. Engraftment was achieved in 94% of the patients in both groups. The PBSC graft contained significantly more nucleated cells, CD34 ؉ , CD3 ؉ , and CD56 ؉ cells (P < .001), and resulted in a significantly shorter time-to-neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 38 publications
(38 reference statements)
7
64
1
3
Order By: Relevance
“…PBSC were already more frequently used than BM (38% vs. 62% of all SCTs), while the stem cell source (BM/PBSC) had no significant influence on survival in multivariate analyses. These data correspond to a retrospective study of Remberger et al, where PBSC and bone marrow from unrelated donors were associated with similar rates of GvHD, relapse, and survival [21]. In contrast, Elmaagacli et al found improved overall survival with PBSC as stem cell source (94% vs. 66%) due to a significantly improved immune reconstitution for PBSCT and a lower TRM consequently to infections and severe aGvHD [22].…”
Section: Comparison Of Patients With Standard and Reduced Intensity Csupporting
confidence: 85%
“…PBSC were already more frequently used than BM (38% vs. 62% of all SCTs), while the stem cell source (BM/PBSC) had no significant influence on survival in multivariate analyses. These data correspond to a retrospective study of Remberger et al, where PBSC and bone marrow from unrelated donors were associated with similar rates of GvHD, relapse, and survival [21]. In contrast, Elmaagacli et al found improved overall survival with PBSC as stem cell source (94% vs. 66%) due to a significantly improved immune reconstitution for PBSCT and a lower TRM consequently to infections and severe aGvHD [22].…”
Section: Comparison Of Patients With Standard and Reduced Intensity Csupporting
confidence: 85%
“…Unfortunately, our study was not able to assess the impact of the graft source on transplantation outcomes according to disease status at transplantation, because only a few patients received transplantation beyond CR1. However, in line with other studies, [20][21][22][23][24][25][27][28][29] our data showed nearly identical outcomes in terms of relapse, NRM, DFS and OS between the two graft sources among transplants in CR1. Therefore, further follow-up with a sizable population is required to define the advantages of URD-SCT using PBSC compared with BM in advanced ALL.…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, except for two studies, 26,28 there was no survival advantage for one graft type over another in the setting of URD-SCT for various hematologic malignancies. [20][21][22][23][24][25]27,29,40 This discrepancy may be attributable to the differences in the sensitivity of underlying disease to graftversus-leukemia effect. According to data from the European Group for Blood and Marrow Transplantation registry, 28 the authors retrospectively compared the use of PBSC (n = 1502) and BM (n = 760) only for AML transplants after myeloablative conditioning transplants URD-SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of peripheral blood stem cells, one would have expected more, not less extensive cGvHD. 28,29 The second important finding of this study relates to the cumulative relapse incidence in the three patient groups. Patients with ATG-F had the highest relapse risk (actuarial risk of relapse at 3 years 41%), followed by those without ATG (31%).…”
Section: Discussionmentioning
confidence: 99%